METHOD OF CALCULATING THE CRITICALITY OF SECTORAL INFOR-MATION AND TELECOMMUNICATION SYSTEMS - Gnatyuk, Sergiy; Sydorenko, Viktoriia; Yudin, Oleksii; Smirnova, Tetiana (Science-based technologies, 2022)
Global trends towards an increase in the number and complexity of cyber-attacks led to the actualization of the issue of information and telecommunication systems (ITS) security. In particular, it is important to sectoral ITS, which are critically important for the functioning of society, the socio-economic development of the state and ensuring the informational component of national security. Taking into account the needs of national security and the need to introduce a systemic approach for solving the problem of critical infrastructure protection, at the national level, creating a security system is one of the priorities in the reforming of the defense and security sector of Ukraine. Thus, there is a need to develop methods and models for the ITS categorization as critical information infrastructure to ensure the national security of Ukraine. The paper presents a method for calculating the level of criticality of sectoral ITS, which, due to the use of a structural-logical and functional model for determining the functional profile of the sectoral ITS security, as well as a functional model for calculating the quantitative criterion for assessing the security of ITS, allow to increase the accuracy of the decision to categorize ITS as critical. The use of the developed method makes it possible to make a decision to categorize ITS as critical, taking into account the properties of information (such as confidentiality, integrity, availability, observability). In addition, an experimental study of the proposed method was carried out on the example of the ITS of the National Confidential Communication System (NCCS), which was used to check the adequacy of the method’s response to changes in input data. Using the method of calculating the criticality of sectoral ITS, the calculation of the criticality ranks for the functionality disruption of components, subsystems and systems of NCCS was carried out; the calculation of the quantitative indicator of the severity of the consequences of the functionality disruption of NCCS, as well as the quantitative indicator of the rank of criticality of NCCS was calculated and a conclusion was made regarding the NCCS criticality.